The Helicobacter pylori GroES Cochaperonin HspA Functions as a Specialized Nickel Chaperone and Sequestration Protein through Its Unique C-Terminal Extension - Schauer, Kristine (American Society for Microbiology (ASM), 2010)
The transition metal nickel plays a central role in the human gastric pathogen Helicobacter pylori because it is required for two enzymes indispensable for colonization, the nickel metalloenzyme urease and [NiFe] hydrogenase. To sustain nickel availability for these metalloenzymes while providing protection from the metal's harmful effects, H. pylori is equipped with several specific nickel-binding proteins. Among these, H. pylori possesses a particular chaperone, HspA, that is a homolog of the highly conserved and essential bacterial heat shock protein GroES. HspA contains a unique His-rich C-terminal extension and was demonstrated to bind nickel in vitro. To investigate the function of this extension in H. pylori, we constructed mutants carrying either a complete deletion or point mutations in critical residues of this domain. All mutants presented a decreased intracellular nickel content measured by inductively coupled plasma mass spectrometry (ICP-MS) and reduced nickel tolerance. While urease activity was unaffected in the mutants, [NiFe] hydrogenase activity was significantly diminished when the C-terminal extension of HspA was mutated. We conclude that H. pylori HspA is involved in intracellular nickel sequestration and detoxification and plays a novel role as a specialized nickel chaperone involved in nickel-dependent maturation of hydrogenase.